Hidden Treasures of Colombia’s Pacific Mangrove: New Fungal Species and Records of Macrofungi (Basidiomycota) - Viviana Motato-Vásquez; Lina Katherine Vinasco-Diaz; Jorge M. Londoño-Caicedo; Ana C. Bolaños-Rojas (Journal of Fungi, 2025)
Mangrove-associated fungi represent a diverse but understudied group of eukaryotic organisms, especially in the Neotropics. The Colombian Pacific region, with approximately 1300 km of coastline covered with 194,880 ha of mangrove forests that remain largely unexplored for macrofungal diversity, is recognized as a global biodiversity hotspot. This study aimed to catalog the macrofungi associated with mangrove ecosystems in Colombia, integrating morphological characterization and molecular phylogenetics, focusing on three Valle del Cauca Pacific coast localities. A total of 81 specimens were collected from both living trees and decaying wood. Detailed macroscopic and microscopic analyses were conducted, and DNA sequences from two ribosomal DNA barcode regions (ITS and LSU) were generated for 43 specimens. Three new species—Neohypochnicium manglarense, Phlebiopsis colombiana, and Porogramme bononiae—were documented. In addition, eight species were reported as new records for both Colombia and mangrove ecosystems, including Microporus affinis, Paramarasmius palmivorus, Phlebiopsis flavidoalba, Porogramme brasiliensis, Resinicium grandisporum, Trametes ellipsospora, T. menziesii, and T. polyzona. Although previously recorded in Colombian terrestrial ecosystems, Lentinus scleropus and Oudemansiella platensis are globally reported here for the first time from mangrove habitats. Furthermore, Fomitopsis nivosella and Punctularia strigosozonata were documented for the first time in Colombia. This study addresses the first exploration of mangrove-associated macrofungi in the country and provides new insights into the hidden fungal diversity and potential of mangrove ecosystems as a latent niche for basidiomycete dispersal along Colombia’s Pacific coast.